Technical note on the removal of a "cold-welded" lag screw from a Trigen Meta-Tan nail. (October 2021) - Yanagisawa, Yohei; Eda, Yusuke; Yamazaki, Masashi
Abstract: Intramedullary or cephalomedullary nail removal often is performed during nonunion reoperations. We have experienced a rare case in which it was difficult to remove the lag screw of the antegrade intramedullary nail, requiring a large amount of force to be applied over a long period. Removal of the lag screw is essential for removal of the nail and subsequent revision surgery. In our case, the lag screw could be removed only by cutting the screw with a carbide drill. For cases in which the nail and lag screw are firmly fixed, surgeons should prepare for the possibility of their separation using a carbide drill. Written informed consent was obtained from the patient for publication of this case report and accompanying images.